SDS-POLYACRYLAMIDE GEL ELECTROPHORESIS OF EQUID SEMINAL PLASMA PROTEINS - ARANGASAMY, A; BHUREA, S K (The Indian Journal of Animal Reproduction, 2023)
Twelve and eight semen ejaculates were obtained from three Marwari and two Exotic Jack (Martinafranc a) stallions, respectively. They were subjected to Plasma separation immediately after collectionby centrifugation at 2000 rpm for 20 minutes and stored at -20° C until analysis. In the seminal plasmathe total protein concentration was estimated by lowry method and molecular weight was determinedby SOS-PAGE analysis. The overall mean values of total protein were recorded as 29.12±2.47 and34.29±1 .44 mg/ml, respectively, in marwari and exotic stallion. Thirteen total protein bands were observedin the range of 17-95 kDa in the Marwari stallion seminal plasma. Thirteen total protein bands wereobserved in the range of 17-101 kDa in the exotic Jack seminal plasma. It can be concluded that among the total proteins, eight protein bands are commonly seen in both the stallion .
Keywords: Marwari; Stallion; Exotic Jack; Seminal plasma; Total protein